PENGUATAN HAK-HAK PEREMPUAN (SEBAGAI BAGIAN DARI HAK ASASI MANUSIA) DALAM KONSTITUSI - Yuli Asmara Triputra (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2017)
The main issue has always been inspiring the development of the principles of a constitutional state is the limitation of the power and protection of human rights. The presence of women in the life of the nation can not be denied. To that end, Indonesian women also need to study and understand their constitutional rights as citizens within the framework of state law. The question is, when talking about women's rights in the constitution, it will be confronted with several obstacles, including public acceptance of it is still very low. In connection with this, then it should be understood implementation of the values of human rights in the constitution. UUD 1945 as Constitution of Indonesia formulated that the protection of human rights is not aimed only at a particular group of people but to every citizen of Indonesia. This is seen from the formulation that uses the phrase